2020
DOI: 10.1038/s41467-020-14548-x
|View full text |Cite
|
Sign up to set email alerts
|

Energy-level quantization and single-photon control of phase slips in YBa2Cu3O7–x nanowires

Abstract: Significant progress has been made in superconducting quantum circuits. However new quantum devices that have longer decoherence times at higher temperatures are urgently required for quantum technologies. Superconducting nanowires with quantum phase slips are promising candidates for use in novel quantum devices. Here, we demonstrate YBa 2 Cu 3 O 7-x nanowires with phase-slip dynamics and study their switching-current statistics at temperatures below 20 K. We apply theoretical models developed for Josephson j… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…There were three attempts of their formation at the current marked in the plot by the higher horizontal red arrow, and possibly one attempt shown by the lower horizontal red arrow. These attempts are consistent with quantum behavior of phase-slip lines in a nanowire made of high-temperature superconductor YBa2Cu3O7-x described in [6]. It shows a certain probability of the switch from superconducting to resistive state from the different quantized energy levels of the system.…”
Section: A Evidence Of Phase Slip Lines In the Brain Slicessupporting
confidence: 85%
See 3 more Smart Citations
“…There were three attempts of their formation at the current marked in the plot by the higher horizontal red arrow, and possibly one attempt shown by the lower horizontal red arrow. These attempts are consistent with quantum behavior of phase-slip lines in a nanowire made of high-temperature superconductor YBa2Cu3O7-x described in [6]. It shows a certain probability of the switch from superconducting to resistive state from the different quantized energy levels of the system.…”
Section: A Evidence Of Phase Slip Lines In the Brain Slicessupporting
confidence: 85%
“…The red line shows position of the zero current. In one and two-dimensional systems, such jumps correspond to phase-slip centers and phase-slip lines, respectively [6,9]. In [10], it was found that the minimal value of these jumps is 2/e, which is equal to the voltage of two nearly merged superconductor -normal metal boundaries.…”
Section: A Evidence Of Phase Slip Lines In the Brain Slicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in superconducting nanowires has also recently increased, due to their possible application in quantum technologies, including quantum sensing and computing. This has been highlighted in the case of YBa 2 Cu 3 O 7-x (YBCO) nanowires with phase-slip dynamics, where evidence of energy-level quantization in the nanowires has been reported [ 7 ]. Moreover, it has also been shown that the absorption of a single photon changes the quantum state of the nanowire, an important result for the development of single-photon detectors with high operating temperature and superior temporal resolution [ 7 ].…”
Section: Introductionmentioning
confidence: 99%